Workshop Aplikasi SIPATEN SOSEK pada Kampung KB Sehati, Kelurahan 5 Ilir, Kecamatan Ilir Timur II, Kota Palembang - Lupikawaty, Marieska; Miskiyah, Neneng; Aprini, Hidayah; Wilianto, Haris; Salman Alfarisi, Kiagus Mohamad; Ramadhanu, Eka Wahyu; Wahyuni, Jelita Sih (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity was motivated by the Sehati Family Planning Village's need for a real-time data monitoring system to evaluate the community's socio-economic resilience. The main challenge faced by partners was the difficulty in monitoring community empowerment indicators effectively and sustainably. The objective of the community service was to implement the website-based SIPATEN-SOSEK (Community Socio-Economic Resilience Monitoring System) application through workshops to increase the capacity of cadres and Working Group (Pokja) administrators. Implementation methods included outreach, technical workshops, mentoring, and data integration with the Village Data House. As a result, cadres and administrators were successfully trained to operate SIPATEN-SOSEK, build a transparent monitoring system, and design data-driven empowerment action plans. This activity successfully created an accountable policy tool and is expected to serve as a model for replication to strengthen the resilience and well-being of families in other Family Planning Villages.